WOUND HEALING ACTIVITY OF ETHANOLIC EXTRACT OF AERIAL AND ROOT PART OF LEPTADENIA PYROTECHNICA (FORSK.) DECNE - NOEL RAHUL SHAW; G K SINGH (International Journal of Pharma and Bio Sciences, 2014)
The ethanolic extracts of aerial and root part of Leptadenia pyrotechnica Plant(Family: Asclepiadaceae), ethnomedicinallyused for the treatment of wounds by the local people of Thar desert, were separately evaluated for wound healing activity on excision wound model, in Wistar albino rats, in the form of an ointment with a concentration (4 % w/w ointment) in simple ointment base. Framycetin sulphate cream (1% w/w) was used as standard drug. The rate of wound healing was assessed by the rate of wound closure and period of epithelialisation. Both the extracts showed significant response in wound healing when compared with the control group.